Mani at the court of the Persian kings : studies on the Chester Beatty Kephalaia Codex - Gardner, Iain. (Nag Hammadi and Manichaean Studies, 2015)
In Mani at the Court of the Persian Kings the authors explore evidence arising from their project to edit the Chester Beatty Kephalaia codex. This new text presents Mani at the heart of Sasanian Iran in dialogue with its sages and nobles, acting as a cultural mediator between East and West and interpreter of Christian, Iranian, and Indian traditions. Nine chapters study Mani's appropriation of the 'law of Zarades' and of Iranian epic; suggest a new understanding of his last days; and analyse his formative role in the history of late antique religions. These interdisciplinary studies advance research in several fields and will be of interest to scholars of Manichaeism, Sasanian Iran, and the development of religions in Late Antiquity.